Influence of curvature radius on the axial crack signal of the magnetic flux leakage detection for tapered roller bearing rings - Yang, Yun; Peng, Guang; Qiu, Shaoxiong; Chen, Cuili; Liang, Zhenyu (Frontiers in Physics, 2023)
Tapered roller bearings are widely used in heavy machinery, railway transportation, aviation, and other fields. Their quality and reliability are related to the operational safety of mechanical equipment. In the axial crack magnetic flux leakage (MFL) detection of the bearing ring, the MFL signals obtained by the sensor from different curvature radii of the surface are inconsistent, affecting the detection accuracy of cracks and subsequent quantitative analysis. In order to address the above problems, the finite element simulation is performed to analyze the influence of the surface curvature radius of the bearing ring on the magnetic field distribution inside the workpiece and the MFL signal in the circumferential magnetization. Through the parallel magnetic circuit, the difference in curvature radius is identified as the basic reason for nonuniform magnetization. On this basis, the compensation method based on the normalization of surface magnetization is proposed. Furthermore, the effectiveness of the compensation method is verified by experiments. The relative change in the amplitude of the crack MFL signal is reduced from 30% to 5%.